"Solution Mining" of Sodium Sulphate - W. A. MacWilliams; R. G. Reynolds (Canadian Institute of Mining, Metallurgy and Petroleum, 1973)
"This paper describes, for the first time, a patented method of extracting sodium sulphate from a natural deposit in Western Canada. The method resembles, but is not, strictly speaking, solution mining. The fact that a plant based on this method has been in successful operation since late 1969 will be of added interest. The deposit in question is located near Metiskow, Alberta, and conventional surface recovery methods could not be applied because of heavy concentrations of mud. Considerable pilot work went into the separation and recovery process on which the plant operation is based. The history of the industry is covered briefly as background to this development. Today it is clear that the method has broader application within the industry and, in concept, may generate interest in many other applications."